To what extent do mesophotic coral ecosystems and shallow reefs share species of conservation interest?. Issue 1 (December 2016) - Laverick, Jack; Andradi-Brown, Dominic; Exton, Dan; Bongaerts, Pim; Bridge, Tom; Lesser, Michael; Pyle, Richard; Slattery, Marc; Wagner, Daniel; Rogers, Alex
Abstract Background Mesophotic coral ecosystems (MCEs) are tropical and sub-tropical reefs between 30 m and potentially >150 m depth, the maximum for photosynthetic hard corals. The definition's upper boundary is ecologically arbitrary. Recently, research has focused on the deep reef refugia hypothesis suggesting MCEs can be protected from shallow-water threats, potentially acting as a local source for re-colonisation of shallow reefs. This led to recent calls to increase their protection. It remains unclear whether the current MCE definition reflects changing biodiversity with depth, and so whether protecting MCEs based on this definition will protect shallow reef species. We ask where shifts in ecological community structure occur across the shallow-mesophotic depth gradient. We consider to what extent MCEs as currently defined protect shallow reef taxa. Research on coral reef depth gradients has a long history. Research relevant to MCEs has been published under a variety of terms. We will use the systematic review framework to collect older data sources, increasing accessibility by depositing the meta-data in an online library for researchers and managers. Methods A systematic review will be conducted, searching online databases, grey literature and personal libraries of experts. The primary question was formulated after consulting an advisory committee. Inclusion criteria discriminate among studies by sampling depths and community data. Critical appraisal of studies will consider key criteria concerning internal validity. We shall identify where more biodiversity and community-level data are required, determined by whether a meta-analysis is possible. Considering how to structure a meta-analysis once community metric and variability data have been collected will help to advise future data collection. Provided enough data are extracted, we shall conduct a meta-analysis examining changes in species richness, abundance and biomass across the depth gradient. If ecological community level data are present, we shall conduct an additional meta-analysis looking at community turnover with depth.